(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Haryana Education Department is running different instructive plans, programs, stipends, bursaries, money related honors, advances grants, co-operations of School Education and Literacy, Elementary Education, Secondary Education, Higher Education, Adult Education, Tribal Education, Technical and Medical Education and Vocational Studies, aptitude improvement and so forth. The unique help is given to the understudies having a place with Scheduled Caste (SC) and Scheduled Tribe (ST), Other Backward Classes (OBC) and Socially, Educationally Backward Classes (SEBC), Minority Category and underneath neediness line (BPL), country territories, and DisabledPhysically Handicapped (PH) understudies.